IMPLEMENTASI DAN EFEKTIVITAS CORPORATE SOCIAL RESPONSIBILITY TERHADAP MASYARAKAT - Helisia Margahana (STIE Atma Bhakti, 2020)
Corporate Social Responsibility (CSR) is a company activity that is carried out with full corporate social responsibility to the environment and the community within the company when carrying out its activities. Many things can be done by the company in implementing its CSR, such as providing funds to create public facilities, scholarships and so on, all of which can improve the welfare of the surrounding community. But in reality there are still many companies that have not realized, so in reality there are still many companies that have not implemented CSR. CSR is a very useful program for companies because companies will become more advanced and sustainable if they maintain relationships with the community. CSR is an investment to encourage the company's growth and development in the future.